Design of Portable Rainfall Simulator Prototype - Suhardi Suhardi; Bambang Marhaenanto; Dedy Wirawan Soedibyo (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
A rainfall simulator is laboratory equipment used to simulate rainfall and replicate the characteristics of natural rain with parameters such as rain intensity, raindrop diameter, rain kinetic energy, rain uniformity coefficient (CU), and rain distribution uniformity (DU). Therefore, this study aims to design a rainfall simulator for rain simulation with good performance. Portable rainfall simulator performance tests include functional tests and performance tests. Functional tests to ensure that the portable rainfall simulator is easy to assemble, lightweight, and functions well. Meanwhile, performance tests are carried out by analyzing rain intensity, raindrop diameter, kinetic energy, uniformity coefficient (CU), and rain distribution uniformity (DU). The results of the study indicate that the rainfall simulator functions well, is easy to assemble, and is lightweight so that it can be applied to various field conditions. Meanwhile, the rainfall simulator performance test shows good performance, with a significant linear relationship existing between pump pressure, rain intensity, raindrop diameter, and kinetic energy. Likewise, the results of the rainfall simulator performance evaluation produce good output with an average of CU and DU greater than 80%. Thus, the portable rainfall simulator functions well and can be used for rainfall simulation.